Upregulated lncRNA Cyclin‐dependent kinase inhibitor 2B antisense RNA 1 induces the proliferation and migration of colorectal cancer by miR-378b/CAPRIN2 axis. Issue 1 (1st January 2021) - Zheng, Yu; Zeng, Jintao; Xia, Haoyun; Wang, Xiangyu; Chen, Hongyuan; Huang, Liangxiang; Zeng, Changqing
ABSTRACT: LncRNA Cyclin‐dependent kinase inhibitor 2B antisense RNA 1 (CDKN2B-AS1) plays a role in the progression of multiple cancers like cholangiocarcinoma, osteosarcoma and several gastrointestinal tumors. Few studies have linked its function and mechanism to the development of colorectal cancer (CRC). The expression of CDKN2B-AS1, microRNA (miR)-378b, and cytoplasmic activation/proliferation-associated protein 2 (CAPRIN2) was analyzed in CRC patients and cell lines. The proliferation and migration of CRC cells were evaluated after gain and loss-of function mutations. Interactions between CDKN2B-AS1 and miR-378b, miR-378b and CAPRIN2 were validated by luciferase reporter, RNA pull-down and RNA immunoprecipitation assays. The role of CDKN2B-AS1 was further confirmed in a xenograft mouse model. We found that the expression of CDKN2B-AS1 and CAPRIN2 was upregulated in CRC and they were linked to the poor differentiation and distant metastasis in CRC patients. CDKN2B-AS1 knockdown attenuated while CDKN2B-AS1 overexpression promoted CRC cell proliferation and migration. Notably, the results of Starbase 2.0 database analysis and in vitro experiments demonstrated that CDKN2B-AS1 could interact with miR-378b and regulate its expression. Furthermore, CAPRIN2 acted as a downstream target of CDKN2B-AS1/miR-378b that involved in modulating β-catenin expression in CRC cells. Upregulation of CDKN2B-AS1 contributed to CRC progression via regulating CAPRIN2 expression by binding to miR-378b. Downregulation of CDKN2B-AS1 suppressed tumor growth and Ki-67 staining in vivo that was related to the miR-378b/CAPRIN2 pathway. This study indicated that lncRNA CDKN2B-AS1 promoted the development of CRC through the miR-378b/CAPRIN2/β-catenin axis. CDKN2B-AS1 might serve as a potential and useful target in CRC diagnosis and treatment.